PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMAN CERITA BIMA BUNGKUS MELALUI STRATEGI PQ4R DENGAN MEDIA POWERPOINT PADA SISWA SMA - Anthik Rowindasari; Raheni Suhita; Budhi Setiawan (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2019)
The purpose of this research is to improve being student active and reading comprehensive skill story of Bima Bungkus by applying PQ4R strategy with media PowerPoint among X MIPA 3 SMA Negeri 3 Boyolali on 2016/2017. The type of this research is a Classroom Action Research, it contains of two cycles. Each cycles consists of four phases, they are planning, acting, observing, and reflecting. Research subject are teacher and X MIPA 3 SMA Negeri 3 Boyolali amoung 36 students. Source of data are derived from report, event of learning and document. Data collection techniques that used are interview, observation, test and documentation. Data validity techniques use data data source triangulasion and method triangulasion. Data analyzed techniques use descripstive comparative analysis technique and critical analysis technique. The conclusion of the research is the applying of PQ4R strategy (Preview, Question, Read, Reflect, Recite, Review) with media PowerPoint can improve being student active and reading comprehension skill of story Bima bungkus among X MIPA 3 SMA Negeri 3 Boyolali.